“The Intensity of Looking” at Karabasz, 2018 - Sapija, Andrzej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The origins of particular documentary films are sometimes difficult to determine, precisely locate and capture in time and space. It is like searching for the source of a river. What marked the beginning of Intensity of Looking, a film about the great documentary film director Kazimierz Karabasz? The beginning of a documentary film’s creation determines the artistic process and elements that shape its strength, energy and main thought. These elements, which sometimes verge on intuition, guide this process, shaping the subject of the film, as well as its meaning, climate and aura. There is a thread connecting the author and the protagonist of the film, something that binds them together during work on the film, and sometimes lasts much longer. The three variants of what initiates the process of making a particular documentary film are as follows. The first is an encounter with a person who could be a character in a documentary film. The second is a thought, idea or problem that a filmmaker wants to address and discuss in a documentary by means of a certain character and story. The third is a return to a character who had been portrayed in a previous documentary film, to tell more about him or her. All three of these variants were the case in the making of Andrzej Sapija’s Intensity of Looking.